Integrated use of plant growth-promoting bacteria and nano-zinc foliar spray is a sustainable approach for wheat biofortification, yield, and zinc use efficiency - Jalal, Arshad [UNESP]; Oliveira, Carlos Eduardo da Silva [UNESP]; Fernandes, Guilherme Carlos [UNESP]; da Silva, Edson Cabral [UNESP]; da Costa, Kaway Nunes [UNESP]; de Souza, Jeferson Silva [UNESP]; Leite, Gabriel da Silva [UNESP]; Biagini, Antonio Leonardo Campos [UNESP]; Galindo, Fernando Shintate [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP] (Frontiers, 2023)
Introduction and aims: The intensive cropping system and imbalance use of chemical fertilizers to pursue high grain production and feed the fast-growing global population has disturbed agricultural sustainability and nutritional security. Understanding micronutrient fertilizer management especially zinc (Zn) through foliar application is a crucial agronomic approach that could improve agronomic biofortification of staple grain crops. The use of plant growth-promoting bacteria (PGPBs) is considered as one of the sustainable and safe strategies that could improve nutrient acquisition and uptake in edible tissues of wheat to combat Zn malnutrition and hidden hunger in humans. Therefore, the objective of this study was to evaluate the best-performing PGPB inoculants in combination with nano-Zn foliar application on the growth, grain yield, and concentration of Zn in shoots and grains, Zn use efficiencies, and estimated Zn intake under wheat cultivation in the tropical savannah of Brazil. Methods: The treatments consisted of four PGPB inoculations (without inoculation, Azospirillum brasilense, Bacillus subtilis, and Pseudomonas fluorescens, applied by seeds) and five Zn doses (0, 0.75, 1.5, 3, and 6 kg ha−1, applied from nano ZnO in two splits by leaf). Results: Inoculation of B. subtilis and P. fluorescens in combination with 1.5 kg ha−1 foliar nano-Zn fertilization increased the concentration of Zn, nitrogen, and phosphorus in the shoot and grain of wheat in the 2019 and 2020 cropping seasons. Shoot dry matter was increased by 5.3% and 5.4% with the inoculation of P. fluorescens, which was statistically not different from the treatments with inoculation of B. subtilis as compared to control. The grain yield of wheat was increased with increasing nano-Zn foliar application up to 5 kg Zn ha−1 with the inoculation of A. brasilense in 2019, and foliar nano-Zn up to a dose of 1.5 kg ha−1 along with the inoculation of P. fluorescens in the 2020 cropping season. The zinc partitioning index was increased with increasing nano Zn application up to 3 kg ha−1 along with the inoculation of P. fluorescens. Zinc use efficiency and applied Zn recovery were improved at low doses of nano-Zn application in combination with the inoculation of A. brasilense, B. subtilis, and P. fluorescens, respectively, as compared to control. Discussion: Therefore, inoculation with B. subtilis and P. fluorescens along with foliar nano-Zn application is considered a sustainable and environmentally safe strategy to increase nutrition, growth, productivity, and Zn biofortification of wheat in tropical savannah.
Keywords: Azospirillum brasilense; Bacillus subtilis; beneficial microorganisms; PGPBs; Pseudomonas fluorescens; Triticum aestivum L.; zinc fertilization